Decoration of A-Ring of a Lupane-Type Triterpenoid with Different Oxygen and Nitrogen Heterocycles - Joana L. C. Sousa; Hélio M. T. Albuquerque; Armando J. D. Silvestre; Artur M. S. Silva (Molecules, 2022)
Betulinic acid (BA) was used as starting building block to create a library of novel BA-derived compounds containing O- and N-heterocycles. Firstly, BA was converted into methyl betulonate (BoOMe), which was used as intermediate in the developed methodologies. 1,2-Oxazine-fused BoOMe compounds were obtained in 12–25% global yields through a Michael addition of nitromethane to methyl (E)-2-benzylidenebetulonate derivatives, followed by nitro group reduction and intramolecular cyclization. Remarkably, the triterpene acts as a diastereoselective inducer in the conjugate addition of nitromethane, originating only one diastereomer out of four possible ones. Furthermore, other oxygen and nitrogen-containing heterocycles were installed at the A-ring of BoOMe, affording 2-amino-3-cyano-4H-pyran-fused BoOMe, diarylpyridine-fused BoOMe and 1,2,3-triazole–BoOMe compounds, using simple and straightforward synthetic methodologies. Finally, BA was revealed to be a versatile starting material, allowing the creation of a molecular diversification of compounds containing a triterpenic scaffold and O- and N-heterocycles.